PARAMETER MORFOLOGI FISIOLOGI DAN KEADAAN KESEHATAN RUSA TIMORENSIS YANG BERADA DI PULAU TIMOR - Wirdateti; Gono Semiadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
Timorensis deer (Cervus timorensis) is one of Indonesian natural resources that has economic and aesthetic values. They are widely distributed from Java island to eastern part of Indonesia. Although the deer is protected by law, however interest in rearing by local people is increasing, such as Timor island. Some people has introduced the deer from the vicinity islands in which from the taxonomical point of view could be a separate sub species. There is no data available on the morphological parameters on this deer in Indonesia, nor about the physiological and health status. The present study was aimed to observed the morphological and physiological parameters and its health status of the timorensis deer under captivity. The result showed that at least there is one sub-species which has introduced to Timor island. Mean of the height was less than 70 cm. Mean chewing rate during rumination was 61/minute with the rate of breathing was 24/minute. Rectal temperature was 37.7oC. Internal parasite was considered negligible.